Struktur Histologis Hepar, Intestinum, dan Ren Burung Cerek Jawa (Charadrius javanicus Chasen 1938) Dengan Kontaminasi DDT di Delta Sungai Progo Yogyakarta - Puspita Sari, Dewi; Hadisusanto, Suwarno; I, Istriyati (Jurusan Biologi UIN Alauddin Makassar, 2014)
Residues of DDT (Dichloro Diphenyl Trichloroethane) in the river environment can get into theÂ Birds body through an intermediary Javan Plover natural feed. Residues of DDT will experienceÂ biomagnification and biotransformation in the body organism. The purpose of this research was toÂ determine residue of DDT in the Progoâs mudflat region, several organs of birds, and their impact onÂ liver, intestine, and kidney Javan Plover. This research was located in Progoâs downstream. TheÂ method of environment and feed sampling done directly on site. The bird sampling using mist nets.Â Detection of residues DDT in environment samples by gas chromatography. Measurement of DDTÂ residues in feed and organs of birds with spectrophotometer. Preparation of histological slide fromÂ liver, intestine, and kidney using paraffin method (with Hematoxilin & Eosin and Mallory AcidÂ Fuchsin staining). Quantitative Data obtained from the measurement results of environment, feed,and organs of Javan Plover samples. Qualitative data analize by descriptively. The analysis showedÂ DDT residues detected in areaâs Progo downstream, natural feed and Javan ploverâs organ. AnalysisÂ shows chronic effects posed by DDT residue on the histological structure of liver, intestine, andÂ kidney of Javan Plover.Keywords: DDT (Dichloro Diphenyl trichloroethane), histological structure, Javan Plover(Charadrius Javanicus Chasen 1938), Progoâs River